Automated tuning of nonlinear model predictive controller by reinforcement learning - Mehndiratta, Mohit (2020)
One of the major challenges of model predictive control (MPC) for robotic applications is the non-trivial weight tuning process while crafting the objective function. This process is often executed using the trial-and-error method by the user. Consequently, the optimality of the weights and the time required for the process become highly dependent on the skill set and experience of the user. In this study, we present a generic and user-independent framework which automates the tuning process by reinforcement learning. The proposed method shows competency in tuning a nonlinear MPC (NMPC) which is employed for trajectory tracking control of aerial robots. It explores the desirable weights within less than an hour in iterative Gazebo simulations running on a standard desktop computer. The real world experiments illustrate that the NMPC weights explored by the proposed method result in a satisfactory trajectory tracking performance.